PARA A DONA DE CASA: COMIDA E IDENTIDADE ENTRE DESCENDENTES DE UCRANIANOS EM PRUDENTÓPOLIS/PR, 1963-1976. - Costenaro, Eliane Crestiane Lupepsa (2013)
The main theme of this research is about the culinary traditions which exist amongst the Ukrainian descendants in Prudentópolis. The main feature and attraction of Prudentópolis City and County as a whole is the Ukrainian immigration. In these culinary traditions, one will actually note the different and peculiar culinary traditions brought to Prudentópolis by the early immigrants. Our resesarch tries to show that these culinary practices aid in the preservation of the ethnic and regional identities. The object of the research was to identify and analyze current traditions and feasts,i.e.,weddings, Christmas and Easter. The core roots of these findings were contributed by the memoires of women selected for the research through oral historical methodologies and culinary receipts published in the Jornal Pracia between the years of 1963 and 1976. We understand that the culinary practices are united with power and with the dynamic process of cultural identity; therefore, these may be understood as elements of identity frontiers and preservation. The sources were analyzed from perspective of the History of the Food.